CHANGES IN THE MECHANICAL COMPOSITION OF IRRIGATED SWAMPY MEADOW SOILS (Scientific journal of the Fergana State University, 2025)
The article presents the results of studies on changes in the granulometric composition of irrigated bog-meadow soils formed in the territory of the Juydam massif of the city of Fergana. It has been proven that according to the content of physical clay (